The Phenomenon of “Indonesia Gelap” on Social Media: Sentiment Analysis and Public Opinion Polarization - Christiany Juditha (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study aims to identify public sentiment and analyze opinion polarization related to the